Involving patients in enrolment decisions for acute myocardial infarction trials. (29th July 2015) - Dickert, Neal W; Miller, Franklin G
Abstract : Seriously ill patients requiring emergency treatment are unlikely to be able to give full informed consent for a clinical trial, but Neal W Dickert and Franklin G Miller argue that this does not mean that they shouldn't be involved in enrolment decisions at all